Human interaction with the surrounding architecture - Chekirova Madina (Theoretical Hypotheses and Empirical Results, 2023)
" Individuals exist, reside, and engage within a physical space. Humanity, having embarked on its journey in the natural world, has actively shaped its own artificial environment throughout its recorded history, in which it has lived and thrived. This constructed environment is known as architectural space. Architecture serves as a tangible testament to the progress of human civilization, encoding the passage of time within the Earth’s spatial domain. During various stages of architectural evolution, human perceptions of themselves and the world have transformed, and creative abilities have become increasingly pronounced. Architectural space represents an artificial, human-made spatial habitat that adheres to the fundamental laws of nature and the objective principles of social development. It constitutes a complex system comprising: 1) Entities originating from nature, human creation, and civilization; 2) Individuals inhabiting this spatial environment and benefiting from its attributes; 3) An ideal (informational) and a material (physical) environment, facilitating interaction between individuals and architecture." Architecture, as a building art, involves the following subject-object relations of humanity and the spatial environment: 1) Comprehension of the natural patterns of spatial behavior; 2) Assimilation of the laws of material creativity and creation in space; 3) Development of spatial consciousness of a professional person. Architecture is a kind of evidence of the intellectual development of man’s spatial consciousness. It can be said that the logic of projecting the temporal flow in the space of the Earth is encoded in the material objects of architecture. As can be seen from the chronological picture of the architectural development of our civilization, there has been a spatial synchronization of socio-political and craft-creative relations in the history of mankind since the beginning of the Renaissance, the line of development has been continuously rushing upward, going beyond the limits of the previously achieved. The last two centuries of architecture and building art are characterized by especially intensive development of samples of architectural form and technologies for its implementation, exceeding the standards of scale and geometric accuracy achieved in the historical past. At certain stages of architectural evolution, a person’s ideas about himself and the world, his creative abilities also changed. The pictorial series of human figures fixing a person’s ideas about himself at various historical moments illustrates and confirms the schematically presented evolution of a person’s spatial consciousness. The physical body of a person, inscribed in a square (cubic) module, determines all visible and invisible structural relations of the 3-dimensional earthly space. The geometric model of the projective space defines the phenomenon of spatial consciousness as a derivative of the projection of the celestial sphere onto the plan of the earth’s surface, which brings divine harmony to man "in the image and likeness."